Polymorphism of 1, 3-X-adamantanes (X = Br, OH, CH3) and the crystal plastic phase formation ability. Issue 7 (29th January 2020) - Negrier, Philippe; Ben Hassine, Bacem; Barrio, Maria; Romanini, Michela; Mondieig, Denise; Tamarit, Josep-Lluis
Abstract : The polymorphism of 1, 3-dimethyladamantane (13DMA), 1, 3-adamantanediol (13DOHA) and 1, 3-dibromoadamantane (13DBrA) has been studied by X-ray powder diffraction, density measurements and differential scanning calorimetry at normal and high-pressure. Abstract : The polymorphism of 1, 3-dimethyladamantane (13DMA), 1, 3-adamantanediol (13DOHA) and 1, 3-dibromoadamantane (13DBrA) has been studied by X-ray powder diffraction, density measurements and differential scanning calorimetry at normal and high-pressure. 13DMA exhibits a low-temperature ordered monoclinic phase (space group P 21 / c, Z = 4, Z ′ = 1) which transforms at 222.6 ± 0.5 K into a high-temperature hexagonal plastic phase ( P 63 / mmc, Z = 26), stable up to the melting point at 246.8 ± 0.5 K at normal pressure. 13DOHA exhibits a low-temperature hexagonal phase ( P 63 / mcm, Z = 6, Z ′ = 0.25) which transforms into a face-centered cubic plastic phase ( Fm 3̄ m ). 13DBrA exhibits a unique ordered orthorhombic phase ( Pnma, Z = 4, Z ′ = 0.5) which remains till the melting point at 382.1 ± 0.5 K. The stability temperature domain of the plastic phases increases with pressure for both 13DMA and 13DOHA. The ability to form the plastic phase for these compounds as well as a series of adamantanes derivatives is analysed through the globularity and asphericity parameters derived from the Hirshfeld surface analysis.